147k views
4 votes
(x - 2)(x² + 2x + 4) = 0​

1 Answer

3 votes

We have to find the value of x from the given equation.

  • (x - 2)(x² - 2x + 2) = 0 is a quadratic equation, so it will have two values.

Step: Write the equation in simplest form.

  • (x - 2)(x² - 2x + 1) = 0

Step: Solve the problem by spiltting method.

  • (x-2)(x² - x -x + 1) = 0
  • (x - 2)(x²-x - x + 1) = 0
  • (x - 2) [x(x - 1) -1(x -1)]
  • (x - 2)[(x-1)(x-1)]

Step: Solve the problem with using algebraic formula.

{x-1](x-1)

Step : We have used a²-b² to solve the problem.

(x-2)(x² - x -x + 1) = 0

(x - 2)(x²-x - x + 1) = 0

(x - 2) [x(x - 1) -1(x -1)]

(x - 2)[(x-1)(x-1)]

Therefore, the possible factorization is (x - 2)[(x-1)(x-1)].

User Gmiley
by
5.6k points